Numerical modelling of large-scale transcurrent faulting and compression effects - Examples from West Africa and New Zealand - (:unkn) unknown (My University, 2016)
The objective of this thesis is to explore the role shear zones play in localization of deformation and exhumation of the lower crust by using a series of 2D and 3D thermo-mechanical numerical models using the West African Craton (WAC) and the Alpine Fault zones as study areas. With respect to the localization of deformation in the upper crust, different orientations of a system of branched strike-slip faults were studied. Under compression boundary conditions, the results show that the internal fault zones as well as the host rocks in between the faults behave as relatively weaker domains than the external regions. Under simple shear boundary conditions, we explored the process of self-organization of the Australian-Pacific plate boundary fault in southern New Zealand. The models show that deformation is focused along narrow high-strain shear zones in the centre of the model when the softening coefficients are high, whereas the strain is more diffuse with many shear zones spread over the model and possibly some high-strain shear zones focused near one border at lower softening coefficients.Regarding the role pre-existing faults and basins play in exhumation of the partially molten lower crust, 2D and 3D models with different boundary conditions were tested (including extension, transtension and compression).- Under extension, in the Eastern and Western parts of the high grade rock corridors in NW Ghana, partially molten rocks exhumed from the lower into middle-upper crustal levels are interpreted to have been dominantly facilitated by the km-scale high-strain corridors. In the central part of the Bole-Bulenga domain, the high grade rocks are interpreted to have been exhumed as a result of a coupling between two mechanisms: (1) the concentration of partially molten rocks between the Jirapa and Bole-Nangodi faults increases due to the reduction in space from north to south; (2) the concentration of lower partially molten rocks in the central part, as a
Keywords: African Research